Opioids for breathlessness: psychological and neural factors influencing response variability. Issue 3 (19th September 2019) - Abdallah, Sara J.; Faull, Olivia K.; Wanigasekera, Vishvarani; Finnegan, Sarah L.; Jensen, Dennis; Pattinson, Kyle T.S.
Chronic breathlessness is a multidimensional and aversive symptom, which is often poorly explained by underlying pathophysiology [1]. For many sufferers, breathlessness is refractory to maximal medical therapies that target disease processes [2]. However, opioids are thought to be a possible therapeutic avenue to treat symptomology independently of disease [3]. Importantly, research in chronic pain has demonstrated that qualities such as anxiety and depression (collectively termed negative affect here) can both exacerbate symptoms [4] and reduce opioid efficacy [5, 6]. Therefore, it may be pertinent to consider such behavioural factors when contemplating the use of opioids for breathlessness. Diminished opioid efficacy in the treatment of breathlessness is related to negative affect and anticipatory brain activity in the anterior cingulate and medial prefrontal cortex. http://bit.ly/2LXyyDo